CHEMICAL AND ORGANOLEPTIC PROPERTIES OF BEKAI (Pycnarrhena tumefacta Miers) LEAVES FOR FLAVOURING AGENT (BIO-VETSIN) - Maharani, Rizki; Fernandes, Andrian; Turjaman, Maman; Kuspradini, Harlinda; Lukmandaru, Ganis (Indonesian Journal of Forestry Research, 2020)
The "tasty" cuisine tends to use chemical flavour agent containing monosodium glutamate (M.S.G.). M.S.G. utilizations, in long-term, may cause health problems, especially triggering cancer cells. Therefore necessary to introducing and increasing a natural flavouring agent to eliminate those health problem, such as bekai leaf. Bekai (Pycnarrhena tumefacta Miers) is familiar as a natural flavour agent (bio-vetsin) in cuisine for forest communities in Nyapa Indah Village, Berau, East Kalimantan, Indonesia. However, until now there has been no proper analysis support for widespread utilization of bekai leaf. This paper studies the presence of phytochemicals, antioxidant and GC MS analysis from bekai leaf extracts, as well as five hedonic classifications of organoleptic test, to reinforce the need for a better understanding of consumers reaction in terms of possible acceptance of additional bekai leaves applied in soup as bio-vetsin. Present study showed that the qualitative screening of phytochemical compounds in bekai leaves ethanolic extracts revealed presence of alkaloids, flavonoids, tannins and steroids. Antioxidants of bekai leaves using 2,2-diphenyl-1-picrylhydrazy (DPPH) method showed that concentrated extract has 80.1%, which predicted can improve immune for inhibitory action of cancer cells. GC MS analysis suspected that bekai leaf extract contained 5 (five) major compounds, i.e. oxirane dodecyl, gamma sitosterol, vitamin E (α tokoferol), 9.12-Octadecadienoic acid (Z,Z)- (natural linoleic acid), and 3-Tetradecanynoic acid (myristic acid). These chemical compound in related with their phytochemical were predicted to contained strong antioxidant activities and some of them commonly used as flavour agent in cuisine for some food industries.